How Do Child-Protection Practitioners Make Decisions in Real-Life Situations? Lessons from the Psychology of Decision Making. (8th January 2018) - Whittaker, Andrew
Abstract: Child-protection social workers must make difficult decisions in real-life circumstances that often involve limited knowledge, uncertainty, time pressures and powerful emotions. These circumstances can pose a significant challenge to reasoning skills, especially when the cost of errors and poor judgement can be unacceptably high. The current study explores the psychological processes that underpin how child-protection practitioners form judgements and make decisions in real-life situations. The study had an ethnographic design with two sites: a local authority children's intake service and a specialist multidisciplinary court assessment service. Twenty-four interviews and forty days of observations were completed. The study found that practitioners' reasoning had a dynamic interplay of intuitive and analytic processes with emotionally informed intuitive processes as the primary driver. Experience played an important role in developing practitioners' reasoning skills. As practitioners became more experienced, they engaged in progressively more sophisticated pattern-recognition and story-building processes to analyse and evaluate complex information. In conclusion, it is argued that greater attention should be given to understanding and supporting practitioner thinking to both support expert practice and reduce errors. An outline of a future research agenda is outlined and the implications for practice are discussed.